A synchronverter‐based static synchronous compensator approach to compensate nonlinear loads in wind integrated power system. (21st June 2020) - Perveen, Rukhsana; Hassan, Arshad; Awais, Muhammad
Summary: The growing trends in the assimilation of renewable energy resources into power system have reduced the power quality and stability of the system. The power quality is mainly concerned with the stability of voltage, frequency, and phase angle, which are enormously affected by the heavy and nonlinear loads. This article presents a new technique of power factor (PF) correction and harmonic compensation notably for nonlinear loads in wind power systems. The controller of proposed model is based on synchronverter topology. The components used for development of the proposed model will be static therefore; it is named as static synchronous compensator (STATCOM). This model shows PF correction with incorporation of renewable source to the STATCOM structure and it also, considers the impact of nonlinear loads and proposes a control topology, and evaluates it. The proposed model is tested using a MATLAB program Simulink. The simulation results of the proposed model show that it can stabilize the PF near to unity under different load scenarios.